Large-Scale Production of Lentiviral Vectors: Current Perspectives and Challenges - Eduardo Martínez-Molina; Carlos Chocarro-Wrona; Daniel Martínez-Moreno; Juan A. Marchal; Houria Boulaiz (MDPI AG, 2020)
Lentiviral vectors (LVs) have gained value over recent years as gene carriers in gene therapy. These viral vectors are safer than what was previously being used for gene transfer and are capable of infecting both dividing and nondividing cells with a long-term expression. This characteristic makes LVs ideal for clinical research, as has been demonstrated with the approval of lentivirus-based gene therapies from the Food and Drug Administration and the European Agency for Medicine. A large number of functional lentiviral particles are required for clinical trials, and large-scale production has been challenging. Therefore, efforts are focused on solving the drawbacks associated with the production and purification of LVsunder current good manufacturing practice. In recent years, we have witnessed the development and optimization of new protocols, packaging cell lines, and culture devices that are very close to reaching the target production level. Here, we review the most recent, efficient, and promising methods for the clinical-scale production ofLVs.